Extending the Shelf-Life of Cocoyam Leaves (Xanthosoma Sagittifolium) Through Blanching, Irradiation and Low Temperature Storage - Afrifa, T. J. (University of Ghana, 2013)
Cocoyam leaf (Xanthosoma sagiitifolium) (‘Kontommire‟) is arguably one of the most readily available and cheap indigenous leafy vegetable that is commonly consumed in Ghana. It is noted to be a good source of minerals, vitamins and soluble fibre when consumed in its fresh (not raw though) state. However, this vegetable is highly perishable. Dehydration methods and jute sack storage are usually used for its preservation. However, these lead to discolouration, loss of some nutrients, and exposure to microbial contamination thus reducing the general acceptability by consumers. In view of this, a study was conducted to process and preserve the leaves in their fresh state. Preservation methods investigated were: refrigeration, steam blanching, gamma irradiation and a combination of these methods. The effect of the various preservation methods on some physicochemical properties (moisture content and dry matter by gravimetric method, vitamin C (ascorbic acid) was determined by iodometric titration method, crude protein was determined by Kjeldahl method, colour change using a Minolta CR310 colorimeter , pH using the Mettler Toledo pH meter (model:T3KfTLH); phytochemical properties (total phenolic using the Folin ciocalteau method and total flavonoids using aluminium chloride colorimetric method); microbial quality (total viable count, total coliforms, yeast and moulds count using serial dilution); consumer acceptance using a 9-point hedonic scale to assess the colour, texture and odour. The best packaging material for effective storage was also investigated. Fresh, fully opened leaves of cocoyam which were two (2) weeks old were collected from the Biotechnology and Nuclear Agriculture Research Institute (BNARI) farm and used for the study. They were decontaminated by washing in fifty (50) % of brine solution and shredded and apportioned for the various treatments, packaged into zip-lock polyethylene bags and hermetically sealed bags. The shelf-life study lasted for three weeks with sampling at weekly intervals. Data obtained were analysed using the Statgraphics Centurion (16th edition). Results showed that, all the preservation methods as well as the packaging materials used increased the moisture content of the fresh cut cocoyam leaves significantly University of Ghana http://ugspace.ug.edu.gh xxi (p<0.05) during storage and reduced the dry matter content. However, the moisture content of samples stored in hermetically sealed polyethylene bag was higher than that of the zip-lock polyethylene bag. Also blanching and its combinations showed significantly (p<0.05) higher moisture content. Vitamin C content also reduced significantly (p<0.05) with all the preservation methods and packaging materials used. However, while the reduction was significantly low in refrigeration (4±2ᵒC) storage and its combinations, it was significantly high in ambient temperature (30±2ᵒC) storage. Radiation doses of 0.5 kGy to 2 kGy also significantly reduced vitamin C. Crude protein content in all the processed leaves increased significantly (p<0.05) during storage but was significantly higher in samples stored in hermetically sealed polyethylene bag. The colour of all the preserved cocoyam leaves was significantly affected by storage. However, the control and samples irradiated at 0.5kGy did not significantly affect the green colour but doses of 1 kGy, 1.5 kGy and 2 kGy reduced the yellowing of the cocoyam leaf under refrigeration storage. Storage increased total phenolic and total flavonoid content in all preservation methods used but had significance only under refrigeration storage and also irradiation dose of 1.5 kGy recorded the highest amount during storage. Microbiological quality assessment of the processed leaves also showed that blanching treatment significantly reduced the total viable count of the cocoyam leaf but increased the yeast and mould growth when stored for longer period. Samples stored in hermetically sealed bag package and ambient temperature (30 ᵒC) also had increase in the total viable count, yeast and mould count and total coliform count during storage. However, refrigeration after irradiation at 0.5 kGy to 1.5 kGy recorded a less count of microbial load in samples stored in hermetically sealed polyethylene bag after two weeks of storage. Pseudomonas fluorescens and Pseudomonas viridiflava, and Citrobacter spp were identified in samples stored by refrigeration.Sensory evaluation of the processed leaves showed that samples stored in zip-lock polyethylene bag were the most acceptable. Refrigeration alone in combination with radiation dose of 0.5 kGy and 1 kGy preserved the cocoyam leaf for three Cocoyam leaf (Xanthosoma sagiitifolium) (‘Kontommire‟) is arguably one of the most readily available and cheap indigenous leafy vegetable that is commonly consumed in Ghana. It is noted to be a good source of minerals, vitamins and soluble fibre when consumed in its fresh (not raw though) state. However, this vegetable is highly perishable. Dehydration methods and jute sack storage are usually used for its preservation. However, these lead to discolouration, loss of some nutrients, and exposure to microbial contamination thus reducing the general acceptability by consumers. In view of this, a study was conducted to process and preserve the leaves in their fresh state. Preservation methods investigated were: refrigeration, steam blanching, gamma irradiation and a combination of these methods. The effect of the various preservation methods on some physicochemical properties (moisture content and dry matter by gravimetric method, vitamin C (ascorbic acid) was determined by iodometric titration method, crude protein was determined by Kjeldahl method, colour change using a Minolta CR310 colorimeter , pH using the Mettler Toledo pH meter (model:T3KfTLH); phytochemical properties (total phenolic using the Folin ciocalteau method and total flavonoids using aluminium chloride colorimetric method); microbial quality (total viable count, total coliforms, yeast and moulds count using serial dilution); consumer acceptance using a 9-point hedonic scale to assess the colour, texture and odour. The best packaging material for effective storage was also investigated. Fresh, fully opened leaves of cocoyam which were two (2) weeks old were collected from the Biotechnology and Nuclear Agriculture Research Institute (BNARI) farm and used for the study. They were decontaminated by washing in fifty (50) % of brine solution and shredded and apportioned for the various treatments, packaged into zip-lock polyethylene bags and hermetically sealed bags. The shelf-life study lasted for three weeks with sampling at weekly intervals. Data obtained were analysed using the Statgraphics Centurion (16th edition). Results showed that, all the preservation methods as well as the packaging materials used increased the moisture content of the fresh cut cocoyam leaves significantly University of Ghana http://ugspace.ug.edu.gh xxi (p<0.05) during storage and reduced the dry matter content. However, the moisture content of samples stored in hermetically sealed polyethylene bag was higher than that of the zip-lock polyethylene bag. Also blanching and its combinations showed significantly (p<0.05) higher moisture content. Vitamin C content also reduced significantly (p<0.05) with all the preservation methods and packaging materials used. However, while the reduction was significantly low in refrigeration (4±2ᵒC) storage and its combinations, it was significantly high in ambient temperature (30±2ᵒC) storage. Radiation doses of 0.5 kGy to 2 kGy also significantly reduced vitamin C. Crude protein content in all the processed leaves increased significantly (p<0.05) during storage but was significantly higher in samples stored in hermetically sealed polyethylene bag. The colour of all the preserved cocoyam leaves was significantly affected by storage. However, the control and samples irradiated at 0.5kGy did not significantly affect the green colour but doses of 1 kGy, 1.5 kGy and 2 kGy reduced the yellowing of the cocoyam leaf under refrigeration storage. Storage increased total phenolic and total flavonoid content in all preservation methods used but had significance only under refrigeration storage and also irradiation dose of 1.5 kGy recorded the highest amount during storage. Microbiological quality assessment of the processed leaves also showed that blanching treatment significantly reduced the total viable count of the cocoyam leaf but increased the yeast and mould growth when stored for longer period. Samples stored in hermetically sealed bag package and ambient temperature (30 ᵒC) also had increase in the total viable count, yeast and mould count and total coliform count during storage. However, refrigeration after irradiation at 0.5 kGy to 1.5 kGy recorded a less count of microbial load in samples stored in hermetically sealed polyethylene bag after two weeks of storage. Pseudomonas fluorescens and Pseudomonas viridiflava, and Citrobacter spp were identified in samples stored by refrigeration.Sensory evaluation of the processed leaves showed that samples stored in zip-lock polyethylene bag were the most acceptable. Refrigeration alone in combination with radiation dose of 0.5 kGy and 1 kGy preserved the cocoyam leaf for three weeks with minimal effect whereas blanching, irradiation only and ambient temperature storage preserved the leaf for only a week. It is recommended that cut-leafy vegetables should be preserved by packaging in zip-lock polyethylene bags and stored in a refrigerator at a temperature of 4± weeks with minimal effect whereas blanching, irradiation only and ambient temperature storage preserved the leaf for only a week. It is recommended that cut-leafy vegetables should be preserved by packaging in zip-lock polyethylene bags and stored in a refrigerator at a temperature of 4±2ᵒC
Thesis (MPhil) - University of Ghana, 2014